Colours of democracy: Trade union banners and the contested articulations of democratic spatial practices. Issue 1 (15th November 2022) - Crossan, John; Featherstone, David; Hayes, Fiona; Hughes, Helen; McDonald, Isobel
Abstract: This paper locates trade union banners and those of other campaigns and left organisations as part of the ongoing work and labour of producing democratic political cultures. It argues that engaging with the ways in which they were used, shaped, produced and re‐worked can shed important light on often neglected spatial practices and forms of agency of democratic politics. We contend that engaging with the geographical imaginaries and practices shaped by trade union engagements with democracy offers important and original perspectives on different articulations of spatial relations, labour, and democratic politics. The paper engages with Clive Barnett's influential work on the geographies of democracy and outlines an alternative position based on engaging with the generative character of political activity. The empirical part of the paper offers three cuts through different articulations of labour and democratic politics. The paper engages with the Banners of Glasgow Shipwrights to explore aspects of trade union politics and struggles for democratic reform. We discuss the relations between the STUC Black Workers' Committee and generative spaces of organising and the relations between banners and the peace movement to engage forms of antagonist democratic cultures. Short Abstract: This paper situates banners, their production, and their diverse uses as part of the ongoing work and labour of producing democratic political cultures. Drawing on a collaborative project on trade unions banners in Glasgow, we argue that engaging with the ways in which banners were used, shaped, produced, and re‐worked can shed important light on the relations between spatial practices and democratic political agency.